The Impact of Grammarly on Enhancing EFL Students' Spelling Competence: The Case of First-Year Students at the University of Souk Ahras - SLAMA Yousra (My University, 2026)
Abstract This study investigates the effect of Grammarly-assisted writing on enhancing the spelling competence of English as a Foreign Language (EFL) students. A total of 30 first-year EFL learners participated in the study, which followed a structured research design comprising a pre-test, six Grammarly-assisted writing sessions using Grammarly, and a post-test. The pre-test established a baseline for spelling accuracy and error types, while the six intermediate sessions provided repeated opportunities for students to practise spelling, receive immediate feedback, and correct errors in phonology, orthography, and morphology. Each session was conducted online via Google Meet, and Grammarly was used to facilitate real-time error detection and correction. As a result of practising spelling using Grammarly-assisted writing and using the spelling rule independently, it had a cumulative effect evaluated by the post-test. The SPSS was used to analyse quantitative data concerning percentages of accuracy and types of errors and descriptive statistics, while applying the repeated-measures ANOVA was used to find significant improvements through different phases. A comparison of error classifications and descriptive statistics reveals a significant improvement in spelling from pre-test to post-test. In other words, the phonological and the orthographic errors are relatively low in the post-test. The Results' analysis reveals the possibility of achieving spelling competency and independent learning through Grammarly-assisted writing, immediate corrective feedback, and independent application of the spelling rules. -------------- الملخص تبحث هذه الدراسة في تأثير ‏الكتابة المدعومة ‏بالذكاء الاصطناعي ‏باستخدام Grammarly على تطوير الكفاءة الإملائية لطلاب اللغة الإنجليزية كلغة أجنبية. شارك في الدراسة 30 طالبًا من السنة الأولى، واتّبع البحث تصميمًا منظمًا يتضمن اختبارًا قبليًا، وست جلسات كتابة مدعومة بالذكاء الاصطناعي باستخدام Grammarly، واختبارًا بعديًا. حدّد الاختبار القبلي مستوى الدقة الإملائية وأنواع الأخطاء، بينما وفّرت الجلسات الست فرصًا متكررة للطلاب لممارسة التهجئة، والحصول على تصحيح فوري، وتصحيح الأخطاء الصوتية والإملائية والصرفية. أُجريت كل جلسة عبر الإنترنت باستخدام Google Meet، واستخدم Grammarly لتسهيل اكتشاف الأخطاء وتصحيحها في الوقت الفعلي. قيّم الاختبار البعدي التأثير التراكمي للتدريب بمساعدة الذكاء الاصطناعي وتطبيق القواعد الإملائية بشكل مستقل. تم تحليل البيانات الكمية، بما في ذلك نسب الدقة، وتصنيف الأخطاء، والإحصاءات الوصفية، باستخدام SPSS، واُستخدم تحليل التباين المتكرر (Repeated Measures ANOVA) لتحديد دلالة التحسن عبر المراحل المختلفة. أظهرت النتائج زيادة كبيرة في الدقة الإملائية من الاختبار القبلي إلى الاختبار البعدي، مع انخفاض واضح في الأخطاء الصوتية والإملائية. تسلط الدراسة الضوء على الإمكانات التربوية لإدماج أدوات الذكاء الاصطناعي في فصول اللغة الإنجليزية كلغة أجنبية، موضحة أن الممارسة المدعومة بالتقنية يمكن أن تعزز مشاركة الطلاب ودقة الكتابة. ----------------------------- Résumé Cette étude examine l’effet de l’écriture assistée par l’IA à l’aide de Grammarly sur le développement de la compétence orthographique des étudiants en anglais langue étrangère (EFL). Un total de 30 étudiants de première année a participé à l’étude, qui a suivi un protocole structuré comprenant un pré-test, six séances d’écriture assistées par l’IA utilisant Grammarly, et un post-test. Le pré-test a permis d’établir le niveau initial de précision orthographique et le type d’erreurs, tandis que les six séances intermédiaires ont offert aux étudiants des occasions répétées de pratiquer l’orthographe, de recevoir un retour immédiat et de corriger les erreurs phonologiques, orthographiques et morphologiques. Chaque séance a été conduite en ligne via Google Meet, et Grammarly a été utilisé pour faciliter la détection et la correction des erreurs en temps réel. Le post-test a évalué les effets cumulatifs de la pratique assistée par l’IA et l’application autonome des règles orthographiques. Les données quantitatives, comprenant les pourcentages de réussite, la classification des erreurs et les statistiques descriptives, ont été analysées avec SPSS, et une ANOVA à mesures répétées a été utilisée pour déterminer la signification des améliorations à travers les différentes étapes. Les résultats montrent une augmentation significative de la précision orthographique entre le pré-test et le post-test, avec une réduction marquée des erreurs phonologiques et orthographiques. L’étude met en évidence le potentiel pédagogique de l’intégration des outils d’IA dans les cours d’anglais langue étrangère, suggérant que la pratique médiatisée par la technologie peut améliorer à la fois l’engagement des apprenants et l’exactitude de l’écriture.
Keywords: Grammarly-assisted writing; EFL students; Immediate feedback; Grammarly; Spelling competence.; الكتابة المدعومة بالذكاء الاصطناعي ، الكفاءة الإملائية، طلاب اللغة الإنجليزية كلغة أجنبية، Grammarly، التغذية الراجعة الفورية; écriture assistée par l’IA; compétence orthographique; étudiants EFL; retour immédia